2021
DOI: 10.1093/ntr/ntab192
|View full text |Cite
|
Sign up to set email alerts
|

Adolescents’ Use of Nicotine-Free and Nicotine E-Cigarettes: A Longitudinal Study of Vaping Transitions and Vaper Characteristics

Abstract: Introduction Although adolescents’ nicotine addiction from e-cigarettes is a concern, few studies differentiate between vaping with and without nicotine. This study examines the prevalence of nicotine and nicotine-free vaping, maps transitions between vaping behaviours, and assesses differences in the personal characteristics of vapers in a sample of Norwegian adolescents. Methods Data came from a nationwide longitudinal stud… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
9
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 13 publications
(11 citation statements)
references
References 45 publications
(63 reference statements)
0
9
1
Order By: Relevance
“…In support of this hypothesis, a past study demonstrated that mice self-administered more green apple-flavored aerosol than unflavored aerosol (Cooper et al ., 2021). Consequently, the self-administration of the flavored vehicle in the present study may mimic human use of zero-nicotine flavored e-liquids, which is common among adolescents (Korfei, 2018; Tokle et al ., 2022). Because the present data from paired vs. unpaired vehicle groups are not sufficient to determine whether flavored aerosol maintained responding, additional research is warranted to examine if the raspberry flavored aerosol is reinforcing for rats by comparing self-administration of raspberry flavored vs. unflavored aerosol.…”
Section: Discussionmentioning
confidence: 99%
“…In support of this hypothesis, a past study demonstrated that mice self-administered more green apple-flavored aerosol than unflavored aerosol (Cooper et al ., 2021). Consequently, the self-administration of the flavored vehicle in the present study may mimic human use of zero-nicotine flavored e-liquids, which is common among adolescents (Korfei, 2018; Tokle et al ., 2022). Because the present data from paired vs. unpaired vehicle groups are not sufficient to determine whether flavored aerosol maintained responding, additional research is warranted to examine if the raspberry flavored aerosol is reinforcing for rats by comparing self-administration of raspberry flavored vs. unflavored aerosol.…”
Section: Discussionmentioning
confidence: 99%
“…The users’ patterns varied somewhat between the countries, and especially, Iceland differed considerably from the other countries, with a very high proportion of single e-cigarette users. Earlier studies have shown connections between use of different tobacco, tobacco-like, and nicotine products among adolescents [ 12 , 23 , 32 , 33 ]. Even though the proportions of dual and triple users varied by country in our study, the results show that multiple substance use is common in all Nordic countries.…”
Section: Discussionmentioning
confidence: 99%
“…Secondly, we do not have data on whether e-cigarettes contained nicotine or not. There could be differences in the use of nicotine and non-nicotine e-liquids between the Nordic countries, as differences have been found between European countries [ 12 , 23 ]. Third, we had to use data for different years (2015 and 2019) to be able to compare all Nordic countries.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations